Le(s) sens et la lecture chez Pascal Quignard : du Lecteur à L’Homme aux trois lettres - Dranenko, Galyna (2022)
This study will attempt to underline the various forms and functions Pascal Quignard assigns to reading in hisdifferent texts. To begin with, we will consider the subtle distinctions and links he creates between silence reading,loneliness reading and wandering reading. In this respect, particular attention will be paid to the relationships which arewoven between reading and loneliness in texts by this solitary and unusual author. In the second part the focus willbe on the evolution of the concept of reading for the author of L’Homme aux trois lettres (2020), who is anxious todevelop an ‘oceanic’ work. Indeed literature as ‘an elusive prey’, according to the author, is not about sense, but aboutthe senses. Finally we shall conclude that in Pascal Quignard’s works, which defy any oversimplified characterizationor classification as far as genres are concerned, reading appears above all as a sensual experiment which leads thereader to some sort of condition close to disappearing and annihilation, in the symbolic or even the mystic senseone can give these terms.
Keywords: Quignard, Pascal